2022
DOI: 10.1097/md.0000000000032231
|View full text |Cite
|
Sign up to set email alerts
|

Whipple’s disease review, prevalence, mortality, and characteristics in the United States: A cross-sectional national inpatient study

Abstract: Whipple's disease is a rare multiorgan systemic disease caused by Tropheryma whipplei infection that may present with a wide range of signs and symptoms. This study aim to comprehensively review and determine the inpatient prevalence, mortality, risk factors, and reasons for hospitalization of patients with Whipple's disease. ICD-10 codes were used to identify admissions with Whipple's disease during the years 2016 to 2018. Characteristics of admissions with and without Whipple's disease were compared. The mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…16 Another American registry-based study found a prevalence of WD of 4.6 per 1 million hospitalizations. 17 A previous study by our group found a prevalence in northern Italy of three WD cases per 1 million inhabitants. 15 Although our sample of 45 patients with WD is certainly worthy of consideration from a clinical point of view, it is nevertheless undeniable that, from a statistical point of view, 45 patients are insufficient to perform a more extensive statistical analysis.…”
Section: Epidemiological Studymentioning
confidence: 69%
See 3 more Smart Citations
“…16 Another American registry-based study found a prevalence of WD of 4.6 per 1 million hospitalizations. 17 A previous study by our group found a prevalence in northern Italy of three WD cases per 1 million inhabitants. 15 Although our sample of 45 patients with WD is certainly worthy of consideration from a clinical point of view, it is nevertheless undeniable that, from a statistical point of view, 45 patients are insufficient to perform a more extensive statistical analysis.…”
Section: Epidemiological Studymentioning
confidence: 69%
“…whipplei infection, including only 18 cases of frank WD, were collected over 20 years 16 . Another American registry‐based study found a prevalence of WD of 4.6 per 1 million hospitalizations 17 . A previous study by our group found a prevalence in northern Italy of three WD cases per 1 million inhabitants 15 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…3 In 1952, it was first thought to be of infectious aetiology as a patient with Whipple’s disease responded to treatment with chloramphenicol, but only in the year 2000, the bacterium was grown and isolated from the heart valve of a patient with blood culture negative endocarditis. 1 3 T. whipplei is present in stool samples of 1%–11% of healthy individuals and in 12%–26% of sewage plant workers; 2 nonetheless it is estimated that less than 0.01% of carriers will develop Whipple’s disease, 4 and that susceptibility depends on host genetic factors, specifically the HLA (human leucocyte antigen) alleles DRB1*13 and DQB1*06, the latter potentially correlated with the immune reconstitution inflammatory syndrome. 1,2,4 Four distinct presentations could be observed: classical Whipple’s disease, localised infection, acute infection and asymptomatic carriage.…”
Section: Introductionmentioning
confidence: 99%